Studying in English at universities in non-English speaking countries: communicative challenges and experiences of educational and cultural adaptation in Lithuania - Grebliauskienė, Beata (2020)
The number of students who decide to enroll in Higher Education Institutions (HEIs) located away from their homeland is increasing every year across the globe. This quantitative change is bringing about a qualitative transformation as the HE sector is becoming one more globalized industry. Together with this growth, the academic offer of study programs delivered in a foreign language (most frequently-English) is also incrementing the level of complexity that HEIs while managing the cultural diversity of the university auditorium. HEIs are naturally lured into his attractive prospect to welcome a larger number of students; however, few are the HEIs truly ready and able to face the challenges that such complex phenomenon implies. A culturally diverse university class can certainly have both positive and negative impact on the teaching and learning processes. The purpose of this article is to explore how foreign students confront the communicational and intercultural challenges they encounter in a predominantly Lithuanian linguistic and cultural environment during their studies delivered in non-native English. The gathered and analyzed empirical data allow to state that there are considerable differences in the experiences and perceptions regarding the causes and possible solutions to the mentioned problems and challenges. The studentswho participated in the focus groups demonstrate contrasting viewpoints compared to those of the interviewed academic and administrative staff members in the receiving HEI.